The effect on cardiopulmonary function after thoracoplasty in pectus carinatum: a systematic literature review. (30th October 2017) - Sigl, Stephan; Del Frari, Barbara; Harasser, Carina; Schwabegger, Anton H
Abstract: OBJECTIVES: Creating an aesthetically appealing result using thoracoplasty, especially when correcting extensive deformities, but only causing low morbidity, is challenging. The frequency of thoracoplasties in cases of pectus carinatum (PC) has increased due to improved experience and modified surgical techniques, resulting in low morbidity and low complication rates. The indications for surgical treatment are still controversial and, in most cases, remain aesthetic or psychological rather than physiological. However, whether cardiopulmonary function changes after surgical repair remains a matter of controversy. We sought to investigate and shed light on published knowledge regarding this question. METHODS: We searched MEDLINE and PubMed databases, using various defined search phrases and inclusion criteria, to identify articles on pre- and postoperative cardiopulmonary evaluation and outcomes. RESULTS: Six studies met the inclusion criteria: 5 studies evaluated patients with PC for cardiopulmonary outcomes after chest wall surgery and 1 did so following conservative compression treatment. In these studies, surgical and conservative correction of PC did not reduce absolute lung volumes and spirometric measurements and consequently had no pathogenic effect on cardiopulmonary function. CONCLUSIONS: The results of this systematic review suggest that surgical correction of PC has no symptomatic pathogenic effect on cardiopulmonary function. The results, however, revealed both heterogeneity in the examinations used and inconsistent methods within each study. Further prospective trials with a stronger methodological design are necessary to objectively confirm that surgical correction of PC does not impair cardiopulmonary function.